End-user involvement in rehabilitation virtual reality implementation research. Issue 2 (17th June 2019) - Proffitt, Rachel; Glegg, Stephanie; Levac, Danielle; Lange, Belinda
Abstract : Purpose: Despite increasing evidence for the effectiveness of off-the-shelf and rehabilitation-specific active video games (AVGs) and virtual reality (VR) systems for rehabilitation, clinical uptake remains poor. A better match between VR/AVG system capabilities and client/therapist needs, through improved end-user involvement (UI) in VR/AVG implementation research, may increase uptake of this technology. The purpose of this paper is to review four case examples from the authors' collective experience of including end users in VR/AVG research to identify common benefits, challenges and lessons learned. Design/methodology/approach: The authors apply knowledge and lessons learned from the four cases to make recommendations for subsequent user-engaged research design and methods, including evaluation of the impact of end UI. Findings: A better match between VR/AVG system capabilities and client/therapist needs leads to improved end UI in all stages of VR/AVG implementation research. There are common benefits of increasing buy-in and soliciting early on the knowledge and skills of therapists as well as input from the ultimate end users: people participating in rehabilitation. Most settings have the challenges of balancing the technology requirements with the needs and goals of the practice setting and of the end users. Research limitations/implications: Increasing end UI in VR/AVG implementation research may address issues related to poor clinical uptake. In the VR/AVG context, end users can be therapists, clients or technology developers/engineers. This paper presented four case scenarios describing the implementation of different VR/AVG systems and involving a variety of populations, end users and settings. Originality/value: The set of recommendations for subsequent user-engaged research design and methods span the process of development, research and implementation. The authors hope that these recommendations will foster collaborations across disciplines, encourage researchers and therapists to adopt VR/AVGs more readily, and lead to efficacious and effective treatment approaches for rehabilitation clients.